NOVEL, SAFE, INDIGENOUS COST-EFFECTIVE INFECTION CONTAINMENT CHAMBER FOR HIGH-RISK AUTOPSIES: THE NEED OF THE HOUR - Johnson, Latif Rajesh; James, Ranjit Immanuel; Rajapandian,; Chander, Prem; Paul, Hema Eunice; Manoj, Daniel (Journal of Forensic Medicine and Toxicology, 2021)
In view of the ongoing pandemic, healthcare workers are rightfully concerned about performing autopsies, due to the risk of infection. An autopsy surgeon and his/her team can inadvertently be exposed to infectious diseases. Use of appropriate personal protective equipment (PPE) and Autopsies are conducted to determine the cause of death either for medicolegal purposes or for medical diagnosis. Available information at a clinical autopsy could vary from very detailed history (including presumptive clinical diagnoses and investigation reports) to absolutely no information regarding the disease or clinical signs of the patient. Thus, during an autopsy, the autopsy surgeon should expect the unexpected. Often, due to the lack of adequate information at the time of autopsy, it is possible that the autopsy surgeon and the team involved in the autopsy are exposed to deadly infectious agents like Rabies, Ebola, Nipah Virus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2), etc.1-3 Therefore, it is preferable that the autopsy surgeon and team be protected from potential exposure to infected bodies, bodily fluids, tissues, contaminated objects, or other contaminated environmental surfaces.4 This would require use of appropriate personal protective equipment (PPE) and performing the autopsy in a autopsy chamber with negative pressure.5-7
Keywords: SARS-CoV-2; healthcare workers; Taking these issues into consideration,